Strategi Disaster Recovery dengan Virtualisasi: Backup dan Restore Sistem Operasi di VMware dengan Menggunakan Snapshot - Rakhmadi Rahman; Anugrah Dwi Ansarna; Eka Tanduklangi (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
A Disaster Recovery Plan (DRP) is a structured approach that describes how an organization can carry out its operations after an unplanned incident that can result in system failure. Creating strong system resilience requires an IT team with strong experience and understanding as well, and this is the background of this research. This research aims to provide practical guidance in implementing disaster recovery strategies with virtualization, especially the snapshot feature on VMware Workstation to test disaster scenarios and evaluate their recovery effectiveness.